Effects of Tamarind Seed on the Growth Performance and Nutrient Digestibility of Porcine - Wea, Redempta; Ninu, Andy Yumina; Dede, Adrianus; Dewi, Elisa; Koten, Bernadete Barek (Faculty of Animal Science, Universitas Brawijaya, 2024)
Pig livestock feed generally competes with human needs; therefore, alternative feed is needed in the form of tamarind seeds, which contain nutrients but are also antinutrients. The technology required was to use fermented liquid feed. This study aimed to examine the effects of tamarind seeds on the nutrient digestibility growth performance of pigs. The study used a randomized blocked design (RBD) with 4 treatments and replications. In the present study, R0 = fermented liquid feed (FLF) without tamarind seeds (TS), R10 = FLF with 10% TS, R20 = FLF with 20% TS, and R30 = FLF with 30% TS. The analyzed data were subjected to analysis of variance and Duncan's test. The research variables were nutrient consumption and nutrient digestive rations. The results showed that increasing the percentage of TS in FLF had no significant effect (P>0.05) on nutrient consumption or crude fat digestibility in Landrace crossed pigs but had a very significant effect (P<0.01) on the digestibility of dry matter, crude protein, nitrogen-free extracts, crude fat, crude fiber, and ash. The conclusion is that tamarind seeds could be used in fermented liquid feed up to 30%, but it is better to use 20% to increase the nutrient digestibility of pigs. Further research regarding its use to determine the performance of carcass production is recommended